A scenario based approach to optimizing cost-effectiveness of physician-staffed Helicopter Emergency Medical Services compared to ground-based Emergency Medical Services in Finland - Axel Ackermann; Jukka Pappinen; Jouni Nurmi; Hilla Nordquist; Anssi Saviluoto; Santtu Mannila; Simo Mäkelä; Paulus Torkki (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2024)
Abstract Objectives Since Helicopter Emergency Medical Services (HEMS) is an expensive resource in terms of unit price compared to ground-based Emergency Medical Service (EMS), it is important to further investigate which methods would allow for the optimization of these services. The aim of this study was to evaluate the cost-effectiveness of physician-staffed HEMS compared to ground-based EMS in developed scenarios with improvements in triage, aviation performance, and the inclusion of ischemic stroke patients. Methods Incremental cost-effectiveness ratio (ICER) was assessed by comparing health outcomes and costs of HEMS versus ground-based EMS across six different scenarios. Estimated 30-day mortality and quality-adjusted life years (QALYs) were used to measure health benefits. Quality-of-Life (QoL) was assessed with EuroQoL instrument, and a one-way sensitivity analysis was carried out across different patient groups. Survival estimates were evaluated from the national FinnHEMS database, with cost analysis based on the most recent financial reports. Results The best outcome was achieved in Scenario 3.1 which included a reduction in over-alerts, aviation performance enhancement, and assessment of ischemic stroke patients. This scenario yielded 1077.07–1436.09 additional QALYs with an ICER of 33,703-44,937 €/QALY. This represented a 27.72% increase in the additional QALYs and a 21.05% reduction in the ICER compared to the current practice. Conclusions The cost-effectiveness of HEMS can be highly improved by adding stroke patients into the dispatch criteria, as the overall costs are fixed, and the cost-effectiveness is determined based on the utilization rate of capacity.